Blockchain Enabled Applications - Understand the Blockchain Ecosystem and How to Make it Work for You (2nd Edition) - Dhillon, Vikram (Research fellow); Metcalf, David (David S.); Hooper, Max (CEO of Merging Traffic) (Apress, an imprint of Springer Nature, 2021)
Work with blockchain and understand its potential application beyond cryptocurrencies in the domains of healthcare, Internet of Things, finance, decentralized organizations, and open science. Featuring case studies and practical insights generated from a start-up spun off from the author's own lab, this book covers a unique mix of topics not found in others and offers insight into how to overcome real hurdles that arise as the market and consumers grow accustomed to blockchain based start-ups. You'll start with a review of the historical origins of blockchain and explore the basic cryptography needed to make the blockchain work for Bitcoin. You will then learn about the technical advancements made in the surrounded ecosystem: the Ethereum virtual machine, Solidity, Colored Coins, the Hyperledger Project, Blockchain-as-a-service offered through IBM, Microsoft and more. This book looks at the consequences of machine-to-machine transactions using the blockchain socially, technologically, economically and politically. This book provides you with a clear perspective of the ecosystem that has developed around the blockchain and the various industries it has penetrated.